Development of Buffer Solution Students’ Worksheet Based on Problem Based Learning with Ethnochemistry to Improve Students’ Science Literacy Ability - Viola Dwicha Asda; Andromeda; Yerimadesi; Hardeli (Jurnal Penelitian Pendidikan IPA, 2023)
Merdeka curriculum emphasizes the ability of students to understand and apply their concepts to solve contextual problems. This research aimed to determine the validity, practicality, and effectivity of buffer solution students’ worksheet based on problem based learning with etnochemistry on students’ science literacy ability. The development model used in this research is 4-D. buffer solution students’ worksheet was validated by 3 chemistry lectures and 2 chemistry teachers. Practicality tests were carried out by 3 chemistry teachers and 32 students. Then, the level of effectiveness of buffer solution students' worksheet is known through the N-gain test. The validity test was analyzed by using aiken's v derived formula consisting the validity of the content and construct which was 0.91 and 0.90 with category valid. The results of the practicality of teachers and students was 88.80 and 87.75 with higher category. Analysis of the n-gain value obtained the results of the value of g = 0.86 in the high category. Then the date analyzed with quantitative method by using hypotheses testing, determined that the research hypothesis was accepted. This result confirmed that buffer solution students’ worksheet based on problem based learning with ethnochemistry was valid, practical, and effective to improving students’ science literacy ability significantly.